Granulocyte-Macrophage Colony Stimulating Factor and Steroid on Neovascularization and Keratinocyte Proliferation in Wound Healing - Naim, Zainul; Supit, Laureen; Sutrisno, Eddy; Buchari, Frank Bietra (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: This study aim to evaluate the effect of subcutaneous application of recombinant human granuloctyte-macrophage colony stimulating factor (rhGM-CSF) around wounds and how it in